Antibiotic-Nigella Sativa Fusion (ANF) as a novel approach intended for the treatment against bacteria forming biofilm in osteomyelitis - Mohamed, Farahidah; Mohd Shafri, Mohd Affendi; Mohd Yusof, Nazri; Harun Ismail, Ahmad Fahmi; Yaacob, Khairul Ikhwan; Yusof, Fatin Athirah; Shahdan, Intan Azura (2015)
Multi-drug resistant bacteria are one of the global problems facing humanity. One of the bacteria of concern causing osteomylitis is Staphylococcus aureus. Biofilm from this bacterium in the infected bones has been clinically isolated from the infected patients. A novel formulation of a contemporary antibiotic i.e Gentamicin (an Aminoglycoside) was fused with prophetic medicine i.e Nigella Sativa oil (NSO) (also known as black seed oil) and thereafter characterised. The fusion was done by preparing the emulsions of the two materials with the aid of varying amount of surfactants. Compatibility testing of the two compositions was also conducted pre and post fusion and pre and post gamma irradiation by Fourier-Transform Infra Red (FTIR), HPLC and Thin Layer Chromatography (TLC). In-vitro efficacy test of the fusion was further tested against both the sensitive and the resistant of the commercial and the clinically isolated S.Aureus. Cell viability was also performed on osteoclast cells to determine preliminary safety profile of the fusion. Results indicate that the fusions are physically and chemically compatible and stable with significantly higher safety level than gentamicin alone. The fusions showed ability to inhibit biofilm formation and are also more effective in-vitro particularly against the resistant S.Aureus unlike Gentamicin. With further clinical proofs, the findings could have high impact on current treatment regimen against multi-drug resistant bacteria particularly for osteomyelitis. It is also pave the way for more antibiotics to be fused with NSO and perhaps other prophetic medicine and tested for the same purpose or others.